2016
DOI: 10.1021/acs.jmedchem.5b01894
|View full text |Cite
|
Sign up to set email alerts
|

An in Vitro and in Vivo Investigation of Bivalent Ligands That Display Preferential Binding and Functional Activity for Different Melanocortin Receptor Homodimers

Abstract: Pharmacological probes for the melanocortin receptors have been utilized for studying various disease states including cancer, sexual function disorders, Alzheimer's disease, social disorders, cachexia, and obesity. This study focused on the design and synthesis of bivalent ligands to target melanocortin receptor homodimers. Lead ligands increased binding affinity by 14- to 25-fold and increased cAMP signaling potency by 3- to 5-fold compared to their monovalent counterparts. Unexpectedly, different bivalent l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
177
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(192 citation statements)
references
References 114 publications
(319 reference statements)
14
177
1
Order By: Relevance
“…From these search parameters, three studies reported selective pA 2 values at two melanocortin receptors (mMC3R and mMC4R) and reported functional agonist EC 50 values for the other two receptors (mMC1R and mMC5R, Table 3) [132-134]. For the sake of clarity, antagonists in Table 3 were divided into two sections: ligands with antagonist activity at the mMC4R but no agonist or antagonist activity observed at the mMC3R at concentrations up to 10 μM (pA 2 < 5) and antagonists that were active at the mMC3R and mMC4R.…”
Section: Selective Compoundsmentioning
confidence: 99%
See 4 more Smart Citations
“…From these search parameters, three studies reported selective pA 2 values at two melanocortin receptors (mMC3R and mMC4R) and reported functional agonist EC 50 values for the other two receptors (mMC1R and mMC5R, Table 3) [132-134]. For the sake of clarity, antagonists in Table 3 were divided into two sections: ligands with antagonist activity at the mMC4R but no agonist or antagonist activity observed at the mMC3R at concentrations up to 10 μM (pA 2 < 5) and antagonists that were active at the mMC3R and mMC4R.…”
Section: Selective Compoundsmentioning
confidence: 99%
“…After the above report, homobivalent ligand development primarily focused on increasing the binding affinity at the hMC4R through various bivalent ligand design strategies [134, 201, 205, 217, 235-242], with some reports focusing on the MC1R and in vivo imaging [134, 243-245]. While high affinity ligands are desirable for biological responses, the use of low affinity pharmacophores in bivalent ligand design allow the greatest detection of synergistic binding [201, 204, 206, 217, 235, 236, 239, 243].…”
Section: Bivalent and Multivalent Melanocortin Ligandsmentioning
confidence: 99%
See 3 more Smart Citations